Chylothorax associated with sarcoidosis: a review of the literature - Israeli-Shani, Lilach; King, Daniel; Epstein Shochet, Gali; Shitrit, David; Wand, Ori (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Objective: To review the medical literature regarding chylothorax associated with sarcoidosis. Methods: A literature review of all reported cases of sarcoidosis-associated chylothorax, we included a novel case report to the analysis. Results: Of sixteen cases included in the study, 10 were women (62.5%), mean age 47±17years. In 6 subjects (37.5%) chylothorax was part of the initial presentation of sarcoidosis. Four subjects (25%) additionally suffered from lymphedema and chylous ascites, and one from chylous ascites only. Thoracic lymphadenopathy was reported for 13/16 subjects (81.3%) and lung parenchymal disease in 8/16 (50%). Compression of the thoracic duct was considered as a causative factor in 10 cases (62.5%). One case was attributed to granulomatous pleural inflammation, one to generalized lymphangiectasia, and no specific causative factors were identified in 4 remaining cases (25%). Overall mortality rate was 18.8% (3/16 subjects). Of note, all the subjects treated with corticosteroids survived. Conclusions: Since the association of sarcoidosis with chylothorax is exceedingly rare, alternative etiologies should be pursued even when chylothorax develops in a subject with preexisting sarcoidosis. However, the possibility of sarcoidosis should be entertained when other etiologies for a newly diagnosed chylothorax are ruled out. A multidisciplinary approach is required for optimal management, both for elucidating the diagnosis and for employing therapy, which could be multimodal. A trial of immunosuppressive therapy with corticosteroids should be considered.